Pengaruh Harga Diri dan Dukungan Sosial terhadap Psychological Well-Being Penyandang Tuna Daksa di Kabupaten Manggarai Barat - Natalia Imakulata Kornely (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Every human being inherently has the hope of living a normal and prosperous life, both physically and psychologically. However, in reality, not all individuals are born with complete physical abilities. Some are born with physical disabilities that limit their ability to perform daily activities. This condition often gives rise to various challenges, especially in the social sphere, as faced by individuals with physical disabilities (tuna daksa). This study aims to examine the relationship between self-esteem and social support with the psychological well-being of persons with physical disabilities in West Manggarai Regency, East Nusa Tenggara Province. The research method used is quantitative with a correlational approach. The population consisted of 37 individuals with physical disabilities, and the total sampling technique was employed. Data collection was conducted using three psychological scales: the psychological well-being scale, the self-esteem scale, and the social support scale. Data analysis was performed using multiple linear regression. The results showed that self-esteem and social support simultaneously had a significant relationship with psychological well-being. Partially, both self-esteem and social support were also found to have significant relationships with psychological well-being. This indicates that psychological well-being in individuals with physical disabilities is influenced by internal factors such as self-esteem, as well as external factors such as social support. The findings of this study can serve as a basis for the development of appropriate psychological and social interventions to improve the quality of life of persons with physical disabilities.